PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP KOMPETENSI SIKAP PESERTA DIDIK (Studi Kasus Di Sma Negeri 78 Jakarta) - Resminingsih, R; Purwanto, P; Suharjadi, S (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This research aims to test and analyze the influence of Pedagogic Competence on the Competence of Student Attitudes at SMAN 78 Jakarta. This study uses a quantitative approach a causality relationship between variables. Data collection technique through questionnaire and pre-research survey with sample 68 Teachers at SMAN 78 Jakarta using nonprobability sampling technique with saturated sampling. Analysis Method using Multiple Linear Regression. The results of this study prove not all variables in teacher pedagogic competence direct influence on Competence Attitude Learners. 2 of 3 The variables studied have direct effect on the students that is variable X1 Know Characteristics and X3 variables Potential Development. The result of competence Attitudes of the strongest Learners is Social Attitude, but simultaneously to the three variables have an influence on Competence Attitude Learners. Variable Development Potential Educative Participants have the greatest influence on the Competence of Social attitudes. Suggestions in this research, Pedagogic Competencies Know Characteristics can be achieved by teachers by identifying Characteristics and providing equal opportunities in learning activities. Potential Development Competencies can be achieved by the teacher by giving attention to each individual, focusing on the interaction and encouraging to understand and use the information conveyed